Zur christologischen Relevanz des Furchtmotivs im Lukasevangelium - Holtz, Gudrun (Biblica, 2009)
The theme of fear is to be found in the gospel of Luke not only in connection with the central revelations of glory — in the account of the birth and transfiguration as well as in the chapter on the resurrection — but also in several miracle stories. In the light of Luke 9,43 Jesus’ mighty deeds, which give rise to fear in those present, appear as the visible aspect of his heavenly glory. This understanding of revelation echoes the revelation theology of the Book of Exodus which interprets the signs and wonders which Israel experiences in the context of the departure from Egypt as the soteriological aspect of God’s glory revealed on Sinai. Jesus as the Holy One of God, who, like the God of Exodus, arouses revelation fear, is to be understood against this background.